The effect of connecting, organizing, reflecting, and extending (core) instruction model by work card toward students’ mathematical problem-solving skill - Tiara Larasati; Lukman El Hakim; Siti Rohmah Rohimah (Pascasarjana Universitas Pendidikan Indonesia, 2019)
The objective of this study was to observe the effect of Connecting, Organizing, Reflecting, and Extending (CORE) instruction model by work card toward students’ mathematical problem-solving skill. The research method was quasi-experiment using non-equivalent post-test only control group design. All classes in seventh grade become the population in SMP Negeri 1 Klari. Two-stage sampling technique, namely purposive sampling and cluster random sampling technique, were used to select VII-A as the experimental class who treated with the CORE instruction model by work card and VII-B as the control class who treated with direct instruction model. Students’ mathematical problem-solving skill was measured by the test which created based on problem-solving skill indicators. The hypothesis was tested using independent sample t-test with a significance value of 0.05. The result of the research shown that there was a significant difference between the experimental and the control class. There was t count = 4.693 > t table = 1.667, so H0 was rejected. This result was indicated that the average of the students’ problem-solving skill who using CORE instruction model by work card higher than the average of the students’ problem-solving skill who using conventional instruction model. Therefore, it can be concluded that CORE instruction model by work card affected students’ mathematical problem-solving skill.